Factors affecting the Herbjcide purchasing decision of Paddy Farmers in Batticatoa District - Viharnaa, S.; Thivahary, G. (ICE 201-3- lnternational Conference of Eastern University, Sri Lanka, 2013)
The advent of herbicides has led to increase in crop yield and reduce drudge;y among farmers. Farmers facing difficulties while deciding and purchasing herbicides regarding to various factors. There are a number of factors influencing farmers' decision in purchasing a herbicide. This study was conducted to find out the different factors that are influencing the herbicide purchasing decision of the paddy growers in Batticaloa district. Hundred number of paddy farmers were rdndomly selected for this study. Questionnaire survey was used as the primary data collection method. Secondary data were collected from published sources. / Based on the study conducted it was found that price of the herbicide is the main factor that influencing the herbicide purchasing decision of the paddy growers in the,district, followed by brand name, quality and effectiveness and-popularity of the herbicides.- Also, the study reveals that most of the paddy farmeFs in the district completely iely on agrochemical traders to get the information related to herbicides. Significant association was observed between the educational level of farmers and purchasing decision based on own experience and based on the discussion with agrochemical traders. Malority of the paddy growers in the study area paid direct cash for purghasing herbicides rather than go for credit purchase. Further more it is also found out that farmers are.getting moreihan 60/o of discount rate from the agrochemical'tradefs during the time of herbicidd' purchasing. Although farmers aware about the toxicity level of the herbicides majority of them were not considered the toxicity level of herbicides at the time of herbicide purchasin$. Thus, establishment of efficient and effective sources of information is importaptto promote correct purchasing herbicides and to promote efficient use of herbicides
Keywords: Agrochemical traders; Herbicides; Paddy growers; Purcfrasing decision